Bilateral Vestibulopathy: Vestibular Function, Dynamic Visual Acuity and Functional Impact - Hermann, Ruben; Ionescu, Eugen C.; Dumas, Olivier; Tringali, Stephane; Truy, Eric; Tilikete, Caroline (Frontiers in Neurology, 2018)
Introduction: Patients suffering from bilateral vestibular hypofunction (BVH) often experience ataxia as well as visual instability. Even though progress has been made in vestibular testing, insights regarding vestibular deficit in BVH remain incomplete since no method allows evaluation of frequency ranges of vestibular sensors in a continuous way. The aim of our study was to give a detailed description of the level of vestibular deficit in different ranges of vestibular stimulation and an exhaustive evaluation of the functional impact including dynamic visual acuity in a cohort of BVH patients in different etiologies. Methods: We prospectively included 20 patients with chronic BVH. All patients underwent clinical evaluation and functional assessment including evaluation of their symptoms related to BVH, quality of life questionnaire and dynamic visual acuity (DVA) in the horizontal and vertical plane. Patients underwent vestibulo-ocular reflex (VOR) testing using rotatory chair, caloric stimulation and video head impulse (vHIT) in the plane of the 6 canals, and cervical and ocular Vestibular evoked myogenic potentials. Results: Mean rotatory VOR gain was 0.07 (SD 0.07). Mean rotatory VOR gain during vHIT for the lateral, anterior and posterior canals was respectively < 0.28, < 0.34 and < 0.20. Mean loss of dynamic visual acuity in the 4 directions was > 0.30 LogMAR. In our population fall frequency was significantly higher in patients with lower Unipedal stance test (UPST), higher Dizziness Handicap Inventory and Ataxia Numeric Scale (ANS) scores, as well as greater loss of upwards DVA. Patients with ototoxic BVH had a significantly higher residual VOR gain during vHIT in the anterior canal plane and lower DHI than other patients. In the general population anterior canal function was significantly higher than lateral or posterior canal function. Conclusion: This study gives extensive descriptive results of residual vestibular function, dynamic visual acuity and quality of life in a population of patients suffering from severe BVH. UPST and ANS are good indicators for fall risk in case of BVH. Gentamicin induced BVH seems to have a lesser impact on quality of life than other etiologies. Anterior semi-circular canal function seems less deteriorated than lateral and posterior function.